Expression and significance of aquaporin protein in sprague-dawley rats after experimental intraventricular hemorrhage - Gu, W; Li, F; Zhang, W; Jia, P (Cellular and Molecular Biology, 2016)
The AQP4 protein in Sprague-Dawley (SD) rats was expressed after experimental intraventricular hemorrhage to investigate the possible pathogenesis of chronic posthemorrhagic hydrocephalus. Seventy SD rats were randomly divided into two groups – sham-operated group (n=35) and experimental group (n=35). Saline and citrated autologous blood were injected into the lateral ventricle of the SD rats in the two groups, respectively. The rats in experimental group were further divided into seven subgroups based on different time points at 3 h, 6 h, 12 h, 1 d, 3 d, 5 d and 7 d. The change of expression of AQP4 protein at different time of bleeding were detected by immumohistochemical techniques and mRNA of AQP4 was observed by in situ hybridization. It was found that 75% rats in experimental group suffered from chronic hydrocephalus at 12 h after intraventricular hemorrhage. High protein expression of AQP4 was observed in the apical of cuboidal epithelium of choroids plexus. The protein expression of AQP4 gradually weakened in experimental group after 3 days of intraventricular hemorrhage and dropped to the minimum at the 7th day, which was significantly different from the control and operative groups (P<0.05). The mRNA expression of AQP4 was weaker than the protein expression, and the locations of expression were generally in agreement with each other.